Is there any association BETWEEN TACSTD2, KIAA1253, Ku70 and mutant kras gene expression and clinical-pathological features of colorectal cancer? - Ghezzi, T.L.; Brum, I.S.; Biolchi, V.; Garicochea, B.; Fillmann, L.S.; Corleta, O.C. (Experimental Oncology, 2011)
Aim of this article is to determine the quantitative gene expression of KRAS codon 12 mutant, TACSTD2, Ku70 and SERIN1 in samples of tumor tissue and to relate them with clinical-pathological characteristics of colorectal cancer.